Manufacturing of Tools and User Assistance for Spice Grinding Machine for Setia SMEs - Demi Ramadian; Addin Akbar; Rizaldi Sardani; Wahyu Fitrianda Mufti; Suci Oktri Viarani (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This research project aims to address operational challenges faced by Setia SME, which specializes in spice sales. Specifically, we aim to design a spice-grinding machine to enhance processing efficiency. Method: We conducted a comprehensive analysis of Setia SME's challenges and formulated a research design that included machine development. Data collection involved surveys, interviews, and on-site observations, analyzed for feasibility. Practical Applications: The successful implementation of the spice grinding machine will boost Setia SME's operational efficiency by eliminating off-site grinding, reducing costs, and increasing production capacity. The technology may benefit other SMEs in the spice industry. Conclusion: This research offers practical solutions to Setia SME's spice processing challenges, demonstrating the value of innovation and technology for SMEs in improving efficiency and sustainability.